Correlated_Random_Walk_Simulations - Martin, Julien; Sabatier, Quentin; Gowan, Timothy A.; Giraud, Christophe; Gurarie, Eliezer; Calleson, C. Scott; Ortega-Ortiz, Joel G.; Deutsch, Charles J.; Rycyk, Athena; Koslovsky, Stacie M. (Dryad Digital Repository, 2015)
This file includes R scripts to estimate encounter rates based on a simulation approach. It includes input information to reproduce results presented in the main text of the paper.